2022
DOI: 10.1111/jfpp.16373
|View full text |Cite
|
Sign up to set email alerts
|

Study on process of Yak and Holstein casein–glucose Maillard reaction and functional properties of their products

Abstract: Process of Maillard reaction within 180 min was studied using Yak and Holstein casein-glucose models by indicators of free amino group consumption, content of H + , amount of intermediate products and browning intensity, while their kinetics were investigated. Intrinsic fluorescence property of casein during Maillard reaction was also measured. Structure and functional properties of Yak and Holstein casein-glucose Maillard reaction products were evaluated. The results showed similar profiles of free amino grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(101 reference statements)
1
2
0
Order By: Relevance
“…3, A 294 increased after glycosylation compared with native EWP, and a similar phenomenon was also observed at A 420 . The larger the XOS/EWP ratio and the longer the reaction time, the larger the A 294 and A 420 values, which was consistent with previous research 18,29 . The A 294 and A 420 values kept increasing during storage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3, A 294 increased after glycosylation compared with native EWP, and a similar phenomenon was also observed at A 420 . The larger the XOS/EWP ratio and the longer the reaction time, the larger the A 294 and A 420 values, which was consistent with previous research 18,29 . The A 294 and A 420 values kept increasing during storage.…”
Section: Resultssupporting
confidence: 92%
“…The larger the XOS/EWP ratio and the longer the reaction time, the larger the A 294 and A 420 values, which was consistent with previous research. 18,29 The A 294 and A 420 values kept increasing during storage. Infant formulas were also showed that the production of the initial, intermediate, and advanced Maillard products increased during simulated consumption storage.…”
Section: Uv-absorbance At 294 Nm and 420 Nmmentioning
confidence: 91%
“…In order to minimize the adverse impact of refrigeration technology on the quality and flavor of crab meat, Liu et al (2018) used edible salt as water-retaining agent and combined with quick-freezing treatment, and the results showed that the muscle quality and flavor of frozen crab were effectively protected [ 42 ]. Modified atmosphere preservation is a preservation technology that inhibits the respiration, growth and reproduction of endogenous microorganisms and enzymatic reaction in aquatic products by adjusting the gas composition and proportion of the environment in which aquatic products are located [ 43 ]. Tang et al (2021) analyzed the effects of air and different gas component packaging methods on the biochemical indexes of cooked crab meat and hepatopancreas, and the results showed that 40 % CO 2 and 60 % N 2 were the best modified atmosphere packaging methods for products under storage conditions at 4 °C [ 44 ].…”
Section: Sustainable Utilization and Problemsmentioning
confidence: 99%